Analisis Kelayakan Usahatani Padi Sawah (Oryza sativa) Sistem Tanam Jajar Legowo (Studi Kasus di Desa Merak Kecamatan Dempet Kabupaten Demak) - Istanto, Istanto; Syekha, Qosim Nur; Subantoro, Renan (Jurusan Agribisnis Fakultas Pertanian Universitas Halu Oleo Kendari Sulawesi Tenggara, 2018)
This study aims to determine the income and feasibility of rice farming with jajar legowo system in Merak Village, Dempet District, Demak Regency. The method used is descriptive method where data collection based on interview, observation, recording, survey through questionnaire, and literature review. The sampling technique was done by purposive sampling method, the respondents used in this research were 40 people (12%) from farmer population amounting to 350 farmers. Rice farming income with jajar legowo system in Merak Village in one planting season is Rp 8,464,910 /ha. The result of analysis shows Revenue of Cost Ratio of paddy field farming on legowo java system of 2.24 or R/C > 1, so the rice farming jajar legowo system in Merak village is feasible to cultivate. Land area affects R/C, narrow land between 0,1-0,5 value RC Ratio 2,08, medium land between 0,51-1 ha value R/C 2,28, land of narrow> 1 ha value R/C 2.48. Thus the more land owned by farmers the higher the R/C value.